Negotiating Parental Mediation as Family Communication Practice in Digitally Mediated Learning - Cahayani Yogaswari (CV. Ulil Albab Corp, 2026)
The integration of digital media into daily life has positioned families as central sites of communication and mediation. The COVID-19 crisis intensified this process, shifting formal education to digitally mediated learning and requiring parents to assume active roles in their children’s education. This study examines how parents of elementary school–aged children in Yogyakarta, Indonesia, negotiated their roles as digital mediators. Using a qualitative multiple case study design involving three families, data were collected through in-depth interviews and direct observations. The analysis focuses on four units: parental attitudes toward technology, mediation practices, family-school relationships, and encountered challenges. Findings indicate that while parents view digital technology as unavoidable, their responses toward its use for learning vary. Parents combined active mediation, restrictive mediation, co-using, and participatory learning based on their digital competencies, time, and school support. Relationships within families and with schools were shaped by communication intensity and parental confidence. Challenges emerged from internal factors, such as limited digital self-efficacy, and external factors, including technological constraints and school demands. Although emergency remote learning has ended, these findings remain relevant for understanding how parental mediation is negotiated in post-crisis family digital communication.